Association Of the Methylene Tetrahydrofolate Reductase (MTHFR) Gene Polymorphism with Susceptibility to Recurrence of Cardiovascular Outcomes Among Ischemic Stroke- A Randomized Controlled Trial - Neetu Kataria; Vasantha C Kalyani; Anissa Atif Mirza; Vivekanandhan S; Mritunjai Kumar; Yogesh Bharupi; Shashi Ranjan; Nitesh Kumar; Niraj Kumar (Medsci Publications, 2022)
Background: Hyperhomocystenemia and genetic variants are factors for causing young age stroke globally. This study aims to identify homocysteine related-MTHFR gene polymorphism that associated with recur-rent cardiovascular outcomes. Methodology: A randomized controlled trial conducted upon 90 hyperhomocysteinemic ischemic stroke patients were taken from the neurology wards of a tertiary care hospital were randomly selected into vita-min B therapy group and control groups (n=45 in each group). Baseline subject details were collected ve-nous blood sample for MTHFR genetic testing via PCR-RFLP technique along with blood homocysteine lev-els, vitamin B12, folic acid levels. Results: The results showed that the frequency of CT genotype polymorphism was 15.5% vs 13.3% for the MTHFR C677T gene without any significant difference between vitamin group and control group respective-ly (p-value >0.05). The reduction in mean homocysteine up to -6.77±4.50 versus -2.08±0.71 µmol/L in the vitamin group as compared to control group respectively, p value 0.001. Conclusion: Considerable amount of MTHFR gene polymorphism found among hyperhomocysteinemic is-chemic stroke of sub-Himalayan region. Nutritional deficiencies including vitamin B 12 & folic acid, and some hidden reasons found, which could lead to the primary cause of hyperhomocysteinemia. Vitamin B therapy is an effective for reducing homocysteine.